Impacts of talent development environments on athlete burnout: a self-determination perspective - Li, C.; Wang, C. K. J.; Pyun, D. Y. (Journal of Sports Sciences, 2017)
Guided by Deci and Ryan`s (2000) self-determination theory, this survey study aimed to examine the effects of the talent development environmental factors on athlete burnout. Talented adolescent athletes (n = 691) filled out a survey form measuring the talent development environmental factors, needs satisfaction and burnout. The findings showed that three talent environmental factors (i.e., long-term development focus, holistic quality preparation and communication) were negative predictors of burnout via needs satisfaction. It was concluded that the three talent development environmental factors may be important for facilitating athletes` needs satisfaction and preventing burnout.